Aedes (Stegomyia) aegypti mosquito bite hypersensitivity in a dog: a case report - Tahir, Djamel (BMC Vet Res, 2020)
BACKGROUND: Mosquitoes are vectors of several pathogens of considerable importance to humans and companion animals, including nematode helminths such as Dirofilaria immitis and Dirofilaria repens that cause heartworm disease and subcutaneous dirofilariosis, respectively. In addition to mosquito-borne pathogen transmission, mosquito bites can cause discomfort and irritation in pets, and even lead to severe hypersensitivity reactions. In the present study, we report an acute local hypersensitivity reaction in a dog following experimental exposure to Aedes (Stegomyia) aegypti. CASE PRESENTATION: A healthy six-year-old male beagle was included in an efficacy study in which dogs (n = 28) were exposed to Ae. aegypti mosquitoes. On Day − 6, the dog was allocated to one of the study groups, consisting of seven dogs to be treated on Day 0 with an imidacloprid/flumethrin collar. After sedation, animals were exposed to approximately 50 females of Ae. aegypti for 60 (± 5) minutes on Days − 6, 1, 7, 14, 21, 28, 55, and 83. On Day − 6, no allergic reaction to the mosquito bites was observed. However, on Day 1, corresponding to the second challenge, the dog demonstrated an acute allergic reaction characterized by swelling of the face (especially in the base of the muzzle and around the eyes), redness of the eyes, and conjunctival edema of the right eye was also observed. The dog was immediately treated with an intramuscular injection of a commercially available antihistamine treatment, Pen-Hista-Strep® containing a suspension of benzylpenicillin, chlorphenamine, dexamethasone, dihydrostreptomycin, and procaine at a dosage of 1 mL per 10 kg. A few hours after treatment, the dog showed noticeable improvement. CONCLUSIONS: This case provides the first evidence of canine acute local hypersensitivity reaction to mosquito bites under laboratory conditions. This observation suggests that invasive mosquito species such as Aedes spp. may affect the health and comfort of our companion animals, especially for pets with outdoor access without individual protective measures against insect bites.